Strategi Guru dalam Mengajarkan Pendidikan Nilai Moral pada Siswa Sekolah Dasar - Asi Faturahma; Fikma Almi Muhti; Lailatur Rahmi (International Forum of Researchers and Lecturers, 2025)
Instilling moral values in elementary school students presents its own challenges in the era of globalization, especially with the emergence of Generation Z, who have distinctive characteristics. This study aims to analyze the strategies employed by teachers in teaching moral education at the elementary level. A descriptive qualitative approach was applied by reviewing relevant literature sources. The findings reveal that teachers play a crucial role as role models and mentors in embedding Pancasila values through active learning, integrating moral values into the curriculum, and utilizing contextual learning media such as folklore rooted in local wisdom. Challenges encountered include environmental influences, limited resources, and students’ low awareness of the importance of morals. This study highlights the need for collaboration among schools, families, and communities, as well as continuous teacher competency development, to foster students with noble character, ethics, and readiness to contribute positively to the nation.